2020
DOI: 10.1021/acsami.9b22967
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SnF2 Addition on the Chemical and Electronic Surface Structure of CsSnBr3

Abstract: We report on the chemical and electronic structure of cesium tin bromide (CsSnBr3) and how it is impacted by the addition of 20 mol % tin fluoride (SnF2) to the precursor solution, using both surface-sensitive lab-based soft X-ray photoelectron spectroscopy (XPS) and near-surface bulk-sensitive synchrotron-based hard XPS (HAXPES). To determine the reproducibility and reliability of conclusions, several (nominally identically prepared) sample sets were investigated. The effects of deposition reproducibility, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 37 publications
3
51
0
12
Order By: Relevance
“…Tin fluoride (SnF 2 ), as the most commonly used additive, has been first used in Pb‐free Sn‐based PSCs, [ 30,38–44 ] in which SnF 2 can effectively inhibit the generation of Sn vacancies, and thus significantly reduce the hole density [ 30,39,45,46 ] by means of SnF 2 itself, [ 30,38,39,42,43 ] SnF 2 ·3FACl (FA = formamidinium), [ 47 ] (SnF 2 (DMSO)) 2 (DMSO = dimethyl sulfoxide), [ 48 ] etc. Inheriting the great success of SnF 2 in Sn‐based PSCs, most of existing low‐ E g mixed SnPb PSCs have employed SnF 2 as one indispensable additive and exploited the functions of the additional additives, but no detailed studies have been reported to comprehensively investigate the roles of such extremely important SnF 2 in both mixed SnPb perovskite absorbers and devices, especially in efficient low‐ E g mixed SnPb PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…Tin fluoride (SnF 2 ), as the most commonly used additive, has been first used in Pb‐free Sn‐based PSCs, [ 30,38–44 ] in which SnF 2 can effectively inhibit the generation of Sn vacancies, and thus significantly reduce the hole density [ 30,39,45,46 ] by means of SnF 2 itself, [ 30,38,39,42,43 ] SnF 2 ·3FACl (FA = formamidinium), [ 47 ] (SnF 2 (DMSO)) 2 (DMSO = dimethyl sulfoxide), [ 48 ] etc. Inheriting the great success of SnF 2 in Sn‐based PSCs, most of existing low‐ E g mixed SnPb PSCs have employed SnF 2 as one indispensable additive and exploited the functions of the additional additives, but no detailed studies have been reported to comprehensively investigate the roles of such extremely important SnF 2 in both mixed SnPb perovskite absorbers and devices, especially in efficient low‐ E g mixed SnPb PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18,47,48] Despite SnF 2 being so widely used, its effects on mixed tinlead perovskites have not previously received comprehensive investigation. Studies on neat-tin perovskites with no alloying of metal cations have explored the influence of SnF 2 on optoelectronic and structural properties of these materials, [49,50] and compared the effects of 0, 5, and 10 mol% addition of SnF 2 . [40] However, these investigations did not consider mixed tin-lead compositions.…”
Section: Introductionmentioning
confidence: 99%
“…used hard X‐ray photoelectron spectroscopy (HAXPES) to indicate that 20 mol% SnF 2 addition increases CsSnBr 3 coverage on the compact TiO 2 (c‐TiO 2 ) substrate confirmed by the vanishing of Ti 3s, 3p, and O 2s shallow core levels of the CsSnBr 3 /c‐TiO 2 samples (Figure 12E). [ 100 ] SnF 2 plays a role in the crystal nucleation process due to the least solubility in common solvent among SnX 2 (X = F, Cl, Br, I) series. [ 101 ] It promotes Sn‐based perovskite nucleation and enables homogeneous crystal growth with full coverage.…”
Section: Additive Engineering Of Sn‐based Pscsmentioning
confidence: 99%